Гуманітарна складова сучасної освіти - Мякшин, А. (ХНУРЕ, 2021)
Today it seems that the initiative of the highest achievements of civilization is nourished by natural and technical research, and humanities knowledge is somewhat inferior in estimates by society. What is the reason for this delusion? And has the humanities really lost touch with the powerful development of scientific and technological advances? Trying to understand this problem is at the same time looking for an answer to a topical question about the mission and strategy of modern education.
Keywords: філософія; гуманітарна складова сучасної освіти